PROFESIONALISME, MOTIVASI KERJA DAN KEPUASAN KERJA SEBAGAI PREDIKTOR KINERJA INTERNAL AUDITOR DI TOYOTA ASTRA MOTOR WILAYAH BALI - Sudiksa, I Wayan; Utama, I Made Karya (E-Jurnal Akuntansi, 2016)
The existence of internal auditor is becoming more important nowadays. As an internal auditor, their main job is now shifting, from internal controller into internal consultant. The objective of this study is to analyze profesionalism, work motivation, and work satisfaction as the predictor of internal auditor’s working satisfaction. The research was conducted in all Toyota Astra Motor main dealers in Bali at the year of 2014 and 43 company’s internal auditor were used as samples. The data was collected using quitionaires and multiple regression analysis was used to analysed data. It shows that profesionalism, work motivation, and work satisfaction have positive impact toward the internal auditors performance. Specifically, 75,3% of those variables affected the internal auditors performance while the rest is affected by other variables does not use in this research.
Keywords: Profesionalism, work motivation, work satisfaction and performance